Levels of autotrophy and heterotrophy in mesophotic corals near the end photic zone - Carmignani, Amy; Radice, Veronica Z.; McMahon, Kathryn M.; Holman, Alex I.; Miller, Karen; Grice, Kliti; Richards, Zoe (Frontiers in Marine Science, 2023)
Mesophotic corals live at 30-150 m depth and can sustain metabolic processes under light-limited conditions by enhancing autotrophy through specialized photoadaptations or increasing heterotrophic nutrient acquisition. These acclimatory processes are often species-specific, however mesophotic ecosystems are largely unexplored and acclimation limits for most species are unknown. This study examined mesophotic coral ecosystems using a remotely operated vehicle (Ashmore Reef, Western Australia at 40–75m depth) to investigate the trophic ecology of five species of scleractinian coral (from genera Leptoseris, Pachyseris, and Craterastrea) using stable isotope analyses (δ13C and δ15N) of host and symbiont tissues and protein concentration. Trophic strategies were analyzed between species and between overall corals sampled above and below the end-photic point, where light is only 1% of surface irradiance. Results showed species-specific differences in resource use. Leptoseris hawaiiensis, L. scabra, and P. speciosa had similar Δ13C values (δ13C host - δ13C symbiont) approaching zero (< 0.5 ‰) which indicated greater dependence on symbiont autotrophy. In contrast, Leptoseris glabra and Craterastrea levis had higher Δ13C values (1.4 to 3.5 ‰) which indicated a greater reliance on external carbon sources. The latter two species also demonstrated tight nitrogen recycling within the holobiont, exhibiting low Δ15N values (host δ15N - symbiont δ15N =< 0.5 ‰), compared to more autotrophic species (Δ15N = >1.2 ‰). Some species demonstrated the ability to maintain metabolic processes despite substantially reduced light availability (0.5 – 2% of surface irradiance). This research challenges our knowledge of acclimation limits for many scleractinian corals and contributes novel information for Ashmore Reef, the Western Australia region and mesophotic ecosystems in general, and critically examines common methods used to interpretate trophic ecology with bulk stable isotopes δ13C and δ15N.